Phylogeography of Schisandra chinensis (Magnoliaceae) Reveal Multiple Refugia With Ample Gene Flow in Northeast China - Ye, Jun-Wei; Zhang, Ze-Kun; Wang, Hong-Fang; Bao, Lei; Ge, Jian-Ping (Frontiers in Plant Science, 2019)
Temperate conifers and broadleaved mixed forests in northeast China are ideal to investigate the genetic consequences of climate changes during the last glacial maximum (LGM), 29–16 thousand years ago (kya). As previous studies were focused on tree species with long generation time; here, the evolutionary history of Schisandra chinensis, a climber species with a generation time of five years, was investigated using chloroplast DNA (cpDNA), nuclear single copy gene (nSCG), and nuclear single sequence repeats (nSSRs, i.e., microsatellite) markers, along with ecological niche modeling (ENM), which predicted a suitable habitat in Korea Peninsula (KP) during the LGM. Private haplotypes and high genetic diversity of both cpDNA and nSCG were mainly found in KP and Changbai Mt. (CB). Although no significant phylogeographic structure was detected in the cpDNA and nSCG, three nSSRs clusters roughly distributed in west (CB and KP), east (north China), and north (Xiaoxing'an Range, XR) regions were found in Structure analysis. The approximate Bayesian computation analysis showed the west cluster diverged at 35.45 kya, and the other two clusters at 19.85 kya. The genetic diversity calculated for each of the three markers showed no significant correlation with latitude. Genetic differentiation of nSSRs was also not correlated with geographic distance. Migrate analysis estimated extensive gene flow between almost all genetic cluster pairs and BOTTLENECK analysis showed that few populations experienced severe bottlenecks. Overall, results indicate that S. chinensis survived the LGM in situ in multiple refugia, which likely include two macrorefugia (KP and CB) and two microrefugia (XR and north China). Extensive postglacial gene flow among the east, north, and west clusters led to uniformly distributed genetic diversity and low genetic differentiation.